A magyar labdarúgás erőtere - Kárász, Dávid Sándor (Közép-Európai Közlemények, 2016)
The aim of this research is to examine the configuration of the Hungarian football based on the 2013-2014 season. The goal of this essay is to provide useful information to the innovation of the Hungarian football on a professional and recreational level. This research discovers the rate of the active footballers in relation to the male population in the Hungarian counties as much as in Budapest, and also figures out the rate of the active professional players among the active players. An analysis of the talent geography is also shown with the support of Ferenc Győri’s indicators (2010). In this analysis we can get useful indicators about the talent launching and talent attracting quality of the regions according to the birthplace of the professional players and the seat of their teams. The talent establishment of the different areas are clearly shown by the difference of these indicators. The research reveals areal anomalies and on the base of these anomalies we can draw a conclusion about the uneven spatial distribution of the several conditions which influence the quality of football. The demonstration of these areal inequalities can help us to discover their reasons and this knowledge can assist to develop football more effectively.